STANDARISASI SPESIFIK DAN NON-SPESIFIK SIMPLISIA DAN EKSTRAK ETANOL RIMPANG KUNYIT (Curcuma domestica Val.) - Cahya, Dayu; Prabowo, Heny (Jurnal Farmasi Udayana, 2019)
Turmeric is a plant that included in Zingiberaceae . Turmerics often used as a traditional medicine to heal wounds, antibacterial, reduces intestine motility, reduce unpleasant body odor, treats fever, diarrhea, and many more. Standardization is performed by examining turmeric rhizome simpicia and extract. Standardization is carried out to guarantee the quality of traditional raw materials and requirements for reproducibility of pharmaceutical and therapeutic qualities. Parameters that have been used in this research are macroscopic test, microscopic test, total ash content test, acid insoluble ash content test, water soluble simplicia content test, ethanol soluble simplicia content test, shrinkage drying test, and Phytochemistry screening qualitatively. From the results, turmeric simplicia has met the requirements, while turmeric extract has  not eligible in requirements, because its acid insoluble ash content are not eligible. This expected because of the impurities which contamine the extract are silica and sand.  Silica can cuts the mucosa of the throat when used it orally. Turmeric extract in this research does not eligible and cannot be used for the next step.